Determinan Kemiskinan Antarwilayah di Sulawesi Tengah - Robby Kamal Fata; Reikha Habibah Yusfi (KOLONI, 2026)
This study aims to analyze the effect of GRDP per capita, Human Development Index (HDI), Gini Ratio, and Open Unemployment Rate (OUR) on the Poverty Rate in Central Sulawesi Province during the 2014–2024 period. The study uses panel data from 13 districts/cities and is analyzed using the First Difference Generalized Method of Moments (FD-GMM). The results show that GRDP per capita and HDI have a negative and significant effect on poverty, while the Gini Ratio and OUR have a positive and significant effect. Meanwhile, the lagged poverty variable does not have a significant effect. These findings indicate that poverty in Central Sulawesi is influenced more by economic factors, human resource quality, income inequality, and labor market conditions than by the poverty level in the previous period.